Implanting suckling heifer calves: growth and subsequent performance - Simms, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 361, suckling, heifer calves was used over a 2-year period to assess the effects of implanting with either Ralgro® or Synovex-C® on growth and subsequent performance as replacement females. Both implants increased (P<.01 ) weaning weights over that of controls, with the weight increase being retained by yearlings. Pelvic area also was increased at 1 year of age by both implants, with Synovex-C producing larger (P<.01) pelvic areas than Ralgro. However, just prior to calving, body weight and pelvic area were similar among treatments. Uterine scores, cycling activity prior to breeding, percentage exhibiting estrus, and pregnancy percentage were similar for all treatments. Implanting tended to reduce first-service conception rates. Synovex-C implanted heifers calved later (P<.05) than Ralgro-implanted heifers and, consequently, their calves tended to be lighter at weaning. Levels of calving difficulty we r e similar for all treatments. In summary, implanting suckling heifer calves at 2-4 months of age will increase growth rate, but this research indicates some potential for reduction in reproductive performance.
Keywords: Beef; Beef heifers; Implants; Ralgro®; Synovex-C®; Calving difficulty